AKIBAT HUKUM PERCERAIAN DAN PROBLEMATIKA PASCA PERCERAIAN - Rahman, Andri Syaiful; Sirri, Rima Alifa (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
Divorce is a legal event that leads to the legal termination of a husband and wife marriage whose legal process is carried out in court. The goal is to protect all rights and obligations that arise as a result of divorce. After the divorce is decided by the court, the divorce will have several legal consequences both for the husband and wife, property, income, family relations and for the children born in the marriage. Related to the obligation to carry out the legal consequences of divorce, often the related parties, namely the husband and wife, do not carry out their obligations in full after the divorce is carried out. Because the divorce process often involves conflicts and legal battles that take time and money. Divorcing couples may become involved in disputes regarding the division of assets, child custody, and financial support. Many problems that often arise after a divorce. This study aims to examine the legal consequences that arise after the occurrence of divorce and examine post-divorce problems that are common in society. This study uses qualitative research methods in descriptive form. Sources of research data through a literature review in the form of a review of reading references in the form of books, research articles/journals, and other reading sources. The results of the study show that there are three legal consequences that arise as a result of divorce. The first is the legal consequences for children. Second, legal consequences for joint assets. Third, legal consequences for livelihood. Common post-divorce problems, for example, often parents, especially the father, are negligent and do not fulfill their obligations to provide for their children.